Detection of reactive oxygen and nitrogen species by upconversion nanoparticle-based near-infrared nanoprobes: recent progress and perspectives - Yu, Xiaokan (2023)
Reactive oxygen species (ROS) and reactive nitrogen species (RNS) are essential oxidative metabolites of organisms, which are closely related to physiological, pathological and pharmacological processes. The accurate detection of ROS/RNS is important for the understanding of biological processes, monitoring of pharmacological effects, and predicting the course of disease. The recently developed NIR nanoprobes based on upconversion nanoparticles (UCNPs) hold great prospects in sensitive and deep-tissue detection of ROS/RNS, and considerable progress has been achieved so far. In this review, we systematically summarize the up-to-date advances of UCNPs-based near-infrared (NIR) probes for ROS/RNS sensing, and the potential challenges and perspectives for further research are also highlighted. We envision that such a research field will have a bright future for modern biomedical applications.